CAPITAL MARKET AND INDUSTRIAL PERFORMANCE NEXUS: Empirical Evidence from Nigeria - Peter F. Offum; Chikulirim E. Ihuoma (The Nigerian Journal of Economic and Social Studies, 2018)
This paper examined the causal relationship between the capital market and the performance of the industrial sector in Nigeria from 1985 to 2015. The paper derived its theoretical basis from the finance-led growth hypothesis and the endogenous growth theory. For empirical analysis, the Phillips-Perron unit root was adopted to determine the time series characteristics of the variables, while causality was examined by employing the Granger causality test approach. Findings revealed that there is a unidirectional causality running from market capitalization ratio and total value of shares traded ratio to industrial performance. The paper recommends improved publicity on the strategic role of the capital market as well as a strong regulatory mechanism for its efficient and smooth operation in order to mobilise long term funds for industrial development in Nigeria.
Keywords: 330; capital market; Granger causality